2015
DOI: 10.1002/pssa.201532500
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and thermoelectric properties of nanocrystalline silicon–germanium alloys

Abstract: The lattice dynamics and thermoelectric properties of sintered phosphorus‐doped nanostructured silicon–germanium alloys obtained by gas‐phase synthesis were studied. Measurements of the density of phonon states by inelastic neutron scattering were combined with measurements of the elastic constants and the low‐temperature heat capacity. A strong influence of nanostructuring and alloying on the lattice dynamics was observed. The thermoelectric transport properties of samples with different doping as well as sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The lattice constant of bulk Si is determined to be 5.50 Å, which agrees well with the theoretical result of 5.48 Å [ 30 ] and the experimental result of 5.43 Å [ 31 ]. As compared with bulk Si, the lattice constant of bulk Ge is larger, i.e., 5.71 Å, which is consistent with the calculated result of 5.65 Å [ 30 ] and the experimental value of 5.77 Å [ 31 ]. Our calculated threshold displacement energies for bulk Si and Ge are summarized in Table 1 , along with the associated defects after the displacement events.…”
Section: Resultssupporting
confidence: 86%
“…The lattice constant of bulk Si is determined to be 5.50 Å, which agrees well with the theoretical result of 5.48 Å [ 30 ] and the experimental result of 5.43 Å [ 31 ]. As compared with bulk Si, the lattice constant of bulk Ge is larger, i.e., 5.71 Å, which is consistent with the calculated result of 5.65 Å [ 30 ] and the experimental value of 5.77 Å [ 31 ]. Our calculated threshold displacement energies for bulk Si and Ge are summarized in Table 1 , along with the associated defects after the displacement events.…”
Section: Resultssupporting
confidence: 86%
“…Other processing techniques such as high pressure torsion [45], hot deformation [46], and liquid phase sintering [47] may be optimized to maximize the amount of internal-strain in the material. The softening effects in Si and Si-Ge alloys by Caudio et al [36,48], and in Bi 2 Te 3 and Sb 2 Te 3 based materials by Klobes et al…”
Section: Engineering Thermal Conductivity Through Lattice Softeningmentioning
confidence: 99%
“…It is observed that the nanocomposite samples exhibit low thermal conductivity as compared to the coarse-grained alloy . Claudio et al measured the density of phonon states using inelastic neutron scattering and concluded that nanostructuring causes an increase in the density of phonon states by enhancing the point defect scattering . The decrease in the thermal conductivity is more pronounced in a transition-metal-doped alloy, which can be attributed to the difference in bond anharmonicities leading to bond heterogeneity in the alloy .…”
Section: Total and Lattice Thermal Conductivity Of Si080ge0184ni0016 ...mentioning
confidence: 99%
“…57 Claudio et al measured the density of phonon states using inelastic neutron scattering and concluded that nanostructuring causes an increase in the density of phonon states by enhancing the point defect scattering. 58 The decrease in the thermal conductivity is more pronounced in a transition-metal-doped alloy, which can be attributed to the difference in bond anharmonicities leading to bond heterogeneity in the alloy. 59 Furthermore, the reduction in Cr-doped alloy can be endorsed to the presence of additional unpaired electrons in Cr to attain half-filled stability of 3d orbitals, which enhances the electron− phonon scattering.…”
mentioning
confidence: 99%